PENGARUH PAJAK, KEPEMILIKAN ASING, BONUS PLAN DAN UKURAN PERUSAHAAN TERHADAP PERUSAHAAN MELAKUKAN TRANSFER PRICING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2014-2018) - Dyah Detari Prabaningrum; Titiek Puji Astuti; Yunus Harjito (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to test empirically the effect of taxes, foreign ownership, bonus plans and company size on transfer pricing in the manufacturing sector listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 period. Based on the purposive sampling method, 33 companies met the criteria to be sampled in the study from 2014-2018. The number of samples in the study for 5 years with 165 observations. This study uses a panel data regression model. Based on the results of data analysis research, it can be concluded that taxes have a positive effect, while foreign ownership, bonus plans, and company size have no effect on transfer pricing in manufacturing companies listed on the Indonesia Stock Exchange in 2014-2018. Keywords: transfer pricing, tax; foreign ownership, the bonus plan, the size of the company